Impact of serological and PCR testing requirements on the selection of COVID‐19 convalescent plasma donors. Issue 5 (8th February 2021) - Carter, Jason A.; Freedenberg, Alex T.; Romeiser, Jamie L.; Talbot, Lillian R.; Browne, Nicholas J.; Cosgrove, Megan E.; Shevik, Margaret E.; Generale, Laura M.; Rago, Molly G.; Caravella, Giuseppina A.; Ahmed, Tahmeena; Mamone, Linda J.; et al.
Abstract: Background: Convalescent plasma is undergoing randomized trials as a potential therapeutic option for COVID‐19 infection. Little empirical evidence exists regarding the determination of donor eligibility and experiences with donor selection. Study Design and Methods: This prospective study was conducted at a tertiary care hospital in New York to select plasma donors for a randomized, double‐blind, controlled convalescent plasma trial. Clearance for donation required successful completion of an online questionnaire and an in‐person screening visit, which included (a) completion of a Donor Health Questionnaire (DHQ), (b) Immunoglobulin G (IgG) antibody testing using an immunochromatographic anti‐ severe acute respiratory coronavirus 2 (SARS‐CoV‐2) test, (c) Polymerase chain reaction (PCR) testing if <28 days from symptom resolution, and (d) routine blood bank testing. Results: After receiving 3093 online questionnaires, 521 individuals presented for in‐person screening visits, with 40.1% (n = 209) fully qualifying. Subjects (n = 312) failed to progress due to the following reasons: disqualifying answer from DHQ (n = 30, 9.6%), insufficient antibodies (n = 198, 63.5%), persistent positive PCR tests (n = 14, 4.5%), and blood donation testing labs (n = 70, 22.4%). Importantly, 24.6% and 11.1% of potential donors who reported having PCR‐diagnosed infection had low or undetectable SARS‐CoV‐2 antibody levels, respectively. Surprisingly, 62.9% (56/89) of subjects had positive PCR tests 14–27 days after symptom resolution, with 13 individuals continuing to be PCR positive after 27 days. Conclusion: It is feasible for a single site to fully qualify a large number of convalescent plasma donors in a short period of time. Among otherwise qualified convalescent plasma donors, we found high rates of low or undetectable antibody levels and many individuals with persistently positive PCR tests.